Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Join our Q&A platform to get precise answers from experts in diverse fields and enhance your understanding. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

. 6x – 3y = 15
4x + 3y = -5
Method of elimination
Helpppppp it’s for a test I have 2 more questions


Sagot :

Answer:

x = 1. y = -3

Step-by-step explanation:

Add the two equations together and notice that all terms containing y will disappear, leaving with

10x = 10 or x = 1

Using this value of x into either one of the equations, you'll get

4(1) + 3y = -5 ---> 3y = -9 or y = -3